Relationship of Bitterness and Laryngeal Movement Revealed Using a Noncontact and Non-invasive Swallowing Function Evaluation Instrument - KAWAHARA, Hitoshi; SHOJI, Toshio; AOKI, Yoshimitsu; FURUUCHI, Hiroshi; TAHATA, Keita; NAKAJIMA, Mai (The Japanese Journal of Dysphagia Rehabilitation, 2015)
Aim:　Meals for patients with dysphagia often consist of soft foods and paste foods. However, these meals rarely match patients’ preference because they are altered not only in shape but also in taste. Meals that stimulate appetite while reducing the risk of mis-swallowing are essential for patients to continue enjoying tasty and safe meals. Therefore, we examined the effect of taste preference on the swallowing function using a non-contact, non-invasive throat organ movement analysis equipment (NESSiE), which permits the quantitative evaluation of laryngeal elevation.Subjects:　Fifty-five healthy adult volunteers (age distribution: 30s, 11; 40s, 11; 50s, 12; 60s, 8; and 70s, 13).Methods:　Each subject tried all 28 flavors of the eating recovery assisting food “i Eat®” and one flavor that each subject liked most was used as the preferred food. The patients underwent the test in a chair in a sitting position with a 70° body angle. The neck was relaxed, and the subjects wore an eye mask to prevent visual information from affecting the sense of taste or mastication. To exclusively evaluate the taste, each subject received a spoonful each of the preferred food and the preferred food supplemented with bitterness to decrease the palatability in the oral cavity, and the subjects were allowed to chew or swallow freely. Swallowing time was measured while the subject ate the preferred food and the bittered food three times each in a random order and six times in total, and the mean for each food was used for the evaluation.Results:　The swallowing time for the bittered food increased significantly in subjects in their 50s and above. No extension was observed in subjects in their 30s or 40s.Conclusion:　The results suggested that the bitterness exerted some effect on the program to encourage smooth swallowing movement through the sensory network for taste and inhibited the movement of masseter muscles during the swallowing movement. In addition, it was suggested that the difference in laryngeal movement caused by preferences such as taste was partially due to the decreased swallowing function, as a result of aging.